2020
DOI: 10.1101/2020.08.25.267328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A unique view of SARS-CoV-2 through the lens of ORF8 protein

Abstract: Immune evasion is one of the unique characteristics of COVID-19 attributed to the ORF8 protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This protein is involved in modulating the host adaptive immunity through downregulating MHC (Major Histocompatibility Complex) molecules and innate immune responses by surpassing the interferon mediated antiviral response of the host. To understand the immune perspective of the host with respect to the ORF8 protein, a comprehensive study of the ORF8 pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…We also tested LL-37s' ability to bind to the negatively charged, secreted accessory protein ORF8, which is unique to SARS-CoV-2 and thus linked to efficient pathogen transmission 36,37 . Multiple functions of ORF8 have been proposed including disruption of antigen presentation via down-regulation of MHC I expression and inhibition of interferon I signaling 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…We also tested LL-37s' ability to bind to the negatively charged, secreted accessory protein ORF8, which is unique to SARS-CoV-2 and thus linked to efficient pathogen transmission 36,37 . Multiple functions of ORF8 have been proposed including disruption of antigen presentation via down-regulation of MHC I expression and inhibition of interferon I signaling 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of mutations, especially in fast evolving genes like ORF8 ( Tan et al, 2020 ) is important not only for pathogenesis and immune modulation but also for drugs and diagnostic tests, especially ORF8 which is one of the viral proteins that has been shown to elicit strong and specific antibody response ( Hachim et al, 2020 ; Wang et al, 2020a ). In this context, ORF8 has been studied not only at the evolutionary level ( Pereira, 2020 ; Chen et al, 2020 ) but also at the mutational one ( Hassan et al, 2020 ), in which only 78 mutations in ORF8 were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three mutations (NS8_L84S, NS8_E92K, and NS8_W45L) in NS8 (ORF8) of SARS-CoV-2, the appearance of E92K has not been reported in earlier studies. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“… 49 Mutation L84S in ORF8 has been associated with decreased stability of ORF8. 44 L84S destabilizes the folding, which may cause upregulation of the host-immune activity 50 ( Figure 5 ). We predicted the stability effect of MTs NS8_E92K and NS8_W45L through DynaMut online server.…”
Section: Resultsmentioning
confidence: 99%